Manipulation of energy and redox states in the C6 glioma cells by buthionine sulfoxamine and N-acetylcysteine and the effect on cell survival to cadmium toxicity - Yang, M.S.; Yu, L.C.; Pat, S.W. (Cellular and Molecular Biology, 2007)
Changes in cellular energy and redox sates were studied in the C6 glioma cells following exposure to chemicals that affect glutathione metabolism. It was demonstrated that treatment with sublethal concentrations (25, 50 and 100 Î¼M) of buthionine sulfoxamine (BSO) did not affect cellular energy state as measured by total adenosine nucleotides (TAN=ATP+ADP+ AMP), ATP:ADP:AMP and energy charge potential (ECP=[ATP + 0.5 (ADP)]/TAN). However, there was a significantly decrease in cellular GSH/GSSG and total glutathione (TG=[GSH+GSSG]/ TAN). The change was due to a significant decrease in intracellular GSH level without significant change in [GSSG]. Cells exposed to BSO for 24 hr were much more sensitive to subsequent injuries caused by Cd (0.6 mM for 3 hr). The results indicated that while a significant reduction of intracellular redox state did not affect cell viability, it could increase the susceptibility of cells to subsequent chemical stress. N-acetylcysteine (NAC), on the other hand, caused a dose (1, 5 and 10 mM)-dependent increase in GSH/GSSG without significant changes in intracellular energy state. Improvement of intracellular GSH/GSSG offered no protection against subsequent Cd induced cell death unless NAC was present at the time Cd was added. The pattern of cell death also correlated with the increase in intracellular free radial generation as measured by the fluorescence labeling with 2ã†’7ã†’- dichlorofluorescin. Results of the present study demonstrated that intracellular redox states could be manipulated by addition of chemicals that affect glutathione metabolism. While the redox state may not be the sufficient condition to cause cell death, it could modulate the response of cells to subsequent Cd treatment. Furthermore, the action of NAC against Cd cytotoxicity may not be related to intracellular redox status.